WOMEN DURING THE JAPANESE OCCUPATION: IN LITERARY NARRATIVES AND MEDIA - Dewojati, Cahyaningrum; Dewi, Alifia Masitha (Prosiding Konferensi Internasional Kesusasteraan, 2025)
During its occupation, Japan sought to win the sympathy of the Indonesian people to gather mass support for its war efforts. Japan attempted to eradicate all Western influences in various fields, including politics, governance, economy, culture, and social order. They also mobilized the people, including women, for Japan's interests. From the beginning, propaganda was a key agenda of the Japanese occupation. Therefore, the Sendenbu propaganda department, part of the Military Government (Gunseikanbu), was established. This article examines the narrative of Indonesian women related to Japanese propaganda from 1942 to 1945 in literary works and media. The emerging narrative generally positions women as propaganda agents, as seen in literary works such as "Citra" by Usmar Ismail, "Kami, Perempoean" by Asia Poetera, and "Pandu Partiwi" by Merayu Sukma. In the media, the portrayal of Indonesian women appears with various missionary images of Sendenbu, evident in publications like "Djawa Baroe" (1943-1945). The approach used in this research is Gérard Genette's narratology theory. The narrative in question refers to discursive narrative, which tells a story or series of events, whether real or fictional, along with the relationships, oppositions, and repetitions related to the portrayal of women in literature and media during that era.